DUOLINGO AS AN EDUCATIONAL LANGUAGE TOOL TO ENHANCE EFL STUDENTS’ MOTIVATION IN WRITING - Alvons Habibie (British : Jurnal Bahasa dan Sastra Inggris, 2020)
Duolingo is one of the modern applications that facilitate acquiring a second language.This research aims at invesitigating students’ motivation in writing through Duolingo as one of educational language tool. This study used descriptive qualitative method to explore and describe the phenomenon. Subjects of this study were 40 students of English department, which consisted of 10 male and 30 female. Data collection techniques in this study were interviews, while the data analysis techniques in this study were data reduction, data presentation, and  conclusions. The study revealed that the use of Duolingo application was quite effective to enhance the students’ motivation in writing. This study showed that Duolingo is an app where every beginner can start learning a second language as it motivates him / her to keep on making progress. Nevertheless, Duolingo also needs improvement to cover more vocabulary, grammar rules and languages, especially English, since it is the lingua franca of the world.